The perceived influence of the learning environment on organisational knowledge creation process and knowledge performance in public research and development organisations in Malaysia / Kamariah Noruddin - Noruddin, Kamariah (2006)
The main objective of this study was to identify the relationships and ways in which the learning environment influences the process of organisational knowledge creation and organisational knowledge performance in public research and development organisations in Malaysia. A unified research model which captured the dimensions of the learning organisation (Watkins and Marsick, 1993) as determinants of the knowledge creation process (Nonaka and Takeuchi, 1995) and its impact on organisational knowledge performance was proposed. The argument put forward in this study was that, knowledge creation process is influenced by an organisational environment in which there is continuous learning, dialogue and inquiry, team learning, embedded systems to support learning, empowerment, leadership support for learning and connection of the environment to the system. The process of knowledge creation through socialisation, externalisation, combination and internalisation was also assumed to have a direct influence on organisational knowledge performance. The study was carried out in three public research and development organisations in the state of Selangor. A key aspect of the research was the use of a combination of quantitative and qualitative methods. The quantitative method played a major part in this study whereby respondents for the survey were selected using a systematic sampling method. The qualitative research was undertaken by conducting on site interviews to facilitate the interpretations of the quantitative results. Results from the quantitative analysis suggested that the influence of the learning environment on organisational knowledge performance was mediated by explicit knowledge process. The results also revealed that explicit knowledge process fully mediated leadership support and systems connection; whilst dialogue and inquiry, continuous learning and embedded systems were partially mediated. Based upon the research findings, a revised final model was then incorporated. The qualitative research began with the initial theoretical framework built from extant literature. The interviews provided further evidence that knowledge creation process could be enhanced in a learning environment. Elements of trust, motivation, work culture and values and resources as proposed by the literature but not included in the survey were uncovered also contributed to empirical evidence (qualitatively). Effective knowledge creation process will contribute to organisational knowledge performance. However, the public sector, where management is more bureaucratic, posed a greater challenge in creating an environment for knowledge management, as a delicate balance has to be attained; on the one hand what is sufficiently open and flexible to allow knowledge processes to flourish and on the other possess enough formality and discipline to ensure that knowledge processes produce tangible outputs which would contribute to organisational improvements.